2016
DOI: 10.1039/c5cp06637a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the electric field during annealing of organic light emitting diodes for improving its on/off ratio

Abstract: If an organic light emitting diode is to be used as part of a matrix addressed array, it should exhibit low reverse leakage current. In this paper we present a method to improve the on/off ratio of such a diode by simultaneous application of heat and electric field post device fabrication. A green OLED with excellent current efficiency was seen to be suffering from a poor on/off ratio of 10(2). After examining several combinations of annealing along with the application of a reverse bias voltage, the on/off ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(40 reference statements)
0
5
0
1
Order By: Relevance
“…1 mA/cm 2 (Figure 5d), is typical of some OLEDs at the device turn-on due to a slight change in material morphological defects caused by the initial current passing through the device. 52…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 mA/cm 2 (Figure 5d), is typical of some OLEDs at the device turn-on due to a slight change in material morphological defects caused by the initial current passing through the device. 52…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to the spin-statistics principle, the ratio of PP S to PP T based on spin pairing within organic electroluminescent devices is 1 : 3. 30,31 In fluorescent devices, S 1, Alq3 generates fluorescence, while T 1 does not contribute directly to the luminescence due to the forbidden transition. It was found that under certain conditions, S 1, Alq3 and T 1, Alq3 can be interconverted, and two T 1, Alq3 can produce an S 1, Alq3 and a ground-state molecule, a process known as TTA, 32–35 creating delayed fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…[45,46] For example, the maximum current efficiency of the OLED using SPW-111 appears at low current density, but the maximum current efficiency of the other OLED using TBADN:DPAVBi appears at high current density. [52,53] As shown in Figure S4 in the Supporting Information, the properties (turnon voltage, luminance at 11 V, and maximum current efficiency) of the e-jet-printed OLEDs with or without the thermal drying process (130 °C for 10 min) were not significantly different. As shown in Table S4 in the Supporting Information, the properties of the e-jet-printed OLED were comparable to the properties in previous results.…”
Section: Wwwadvancedsciencecommentioning
confidence: 96%
“…Also, the processing steps of this hybrid 3D printing system require no additional thermal drying/annealing steps immediately after the materials were printed because our e‐jet system uses fine nozzles to facilitate the ejection of small droplets, which are dried very quickly during their flight . However, additional thermal treatments of the fully fabricated OLEDs can improve the device performances further by enhancing the diffusivity of carriers . As shown in Figure S4 in the Supporting Information, the properties (turn‐on voltage, luminance at 11 V, and maximum current efficiency) of the e‐jet‐printed OLEDs with or without the thermal drying process (130 °C for 10 min) were not significantly different.…”
mentioning
confidence: 99%